Study of Extent of Removal of Lead, Copper, and Zinc in the Tap Water Using Tea Leaves - Azizan, Nurazira (Universiti Sains Malaysia, 2006)
The extent of removal of copper, lead and zinc in tap water by using tea leaves had been studied. The tap water usually contains some amount of copper, lead and zinc. The concentration of the copper, lead and zinc in the tap water was determined by atomic absorption spectrometer. After that, tea was prepared using the same tap water. Then, the concentration of the metals in the tea was determined by using the atomic absorption spedrometer again. The concentration of the metals in the water before and after preparing the tea was compared. It was expected that the tea leaves will remove some amount of the metals of concern. The results showed that tea leaves in tea-bags could remove 21.2% of lead and 63. 1 % of zinc; medium tea leaves could remove 18.2 % of lead and 75.1 % of zinc; and large tea leaves could remove 16.5 o/o of lead and 83.1 o/o of zinc. However, the results have shown that the concentration of copper in the tea has increased after the tea was prepared. The concentration of the copper has increased by 0.041 mg/L, 0.019 mg/L, and 0.013 mg/L in tea prepared using teabags, medium-sized tea leaves and large tea leaves, respectively.